Object-Oriented Software for Fitness-For-Service Assessment of Cracked Cylinder Based on API RP 579 (Fracture and Structural Integrity, 2020)
Fitness-for-service assessment of a cracked component intends to evaluate its remaining strength and remaining life to support the implementation of a maintenance plan. This research aims to develop a fitness-for-service assessment software to facilitate the task. The software development process included identifying the software specifications, designing the software structure, manipulating the information from the standard for programming, the graphical user interface design, and finally verification of the software. The assessment procedure employed in this study was the third edition of the standard API RP 579. The software structure was designed using an object-oriented concept. The software can perform integrity assessment levels 1, 2, and 3 option B, leak-before-break assessment, and remaining life assessment for a cracked cylinder that has a through-thickness crack or semi-elliptical surface crack oriented in an axial or circumferential direction. The applied loads could be a nominal axial force, bending moment, and internal pressure, as well as stress profiles perpendicular to the crack plane due to mechanical, thermal, and residual stresses. Accuracy of the software was demonstrated by applying it to example problems. Some aspects of the software extensibility were conceptually discussed.
Keywords: API 579; Object-Oriented programming; Fitness-for-Service; Fracture mechanics; Pressure vessel